Edukasi Perawatan Payudara Dalam Upaya Meningkatkan Efikasi Diri Menyusui pada Ibu Hamil Trimester Akhir - Sianturi, Elly; Siregar, Marni (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
Breast milk (ASI) is the best food for infants up to six months old, supporting their growth and development. Gastrointestinal infections such as diarrhea, caused by unhygienic milk and bottle preparation, can lead to dehydration and malnutrition, thereby increasing the risk of stunting. Breastfeeding self-efficacy refers to a mother's confidence in her ability to breastfeed her baby. Research shows that mothers who do not practice exclusive breastfeeding in North Tapanuli Regency have low self-efficacy, at 58.90% (Sianturi, 2023). Knowledge and breastfeeding self-efficacy should be established during pregnancy so that once the baby is born, particularly in the first hour of life, the baby can immediately receive breast milk as a vital source of life. This community service activity was conducted at the Parbaju Julu Village Head Office in Tarutung, targeting 31 third-trimester pregnant women from the working area of the Hutabaginda Public Health Center. The method used in this program included lectures with Q&A sessions about breast anatomy and breastfeeding using PowerPoint media, as well as demonstrations on breast care and solutions to breastfeeding problems using a breast model, towel, baby oil, pillow, washcloth, warm and cold water basins, and baby dolls. The team also explored the experiences of pregnant women, especially multigravida mothers, regarding breastfeeding challenges. A post-test was conducted to assess changes in breastfeeding knowledge and self-efficacy after the educational session, and the results showed that 29 mothers (76.31%) had good knowledge and 31 mothers (81.57%) had high breastfeeding self-efficacy. The education proved effective in increasing breastfeeding knowledge and self-efficacy among women in their third trimester of pregnancy. Keywords: Breastfeeding self-efficacy, Maternal knowledge, Health education, Third trimester, Stunting.